Assessment of the effect of intravitreal triamcinolone acetonide on the chorioretinal and vitreous inflammatory reaction to cryotherapy in rabbits - Figueirêdo,Eugênio Santana de (2012)
PURPOSE: To evaluate the inflammatory response in the choroid, retina and vitreous in rabbit eyes underwent cryotherapy followed by intravitreal triamcinolone acetonide and to compare with those underwent cryotherapy followed by intravitreal injection of saline solution. METHODS: This is a prospective case-control study. Surgical procedures were performed in eleven rabbits. Two animals were excluded because they did not complete the postoperative period or had intraoperative or postoperative complications. All rabbits underwent superior temporal peritomy and transscleralcryotherapy in both eyes. After cryotherapy, animals received intravitreal injection of triamcinolone acetonide in one eye and saline solution in the fellow eye. Animals were sacrificed seven days after the procedure and their eyes were enucleated. Histological sections of eyeballs were prepared and the vitreous humor was aspirated. The count of inflammatory cells was performed by light microscopy. RESULTS: Histological sections of both eyes of nine rabbits were analyzed. Inflammatory cells were found only in the choroid. There was no statistically significant difference in the number of inflammatory cells between the two groups, regardless of cell type analyzed. CONCLUSION: This study showed no statistically significant difference between the use or absence of intravitreal triamcinolone acetonide in the inflammatory response to cryotherapy in rabbit eyes. Studies with larger samples are needed to confirm the trend of this paper.